2021
DOI: 10.3389/fcvm.2021.599545
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy Is Associated With an Increased Risk of Carotid Plaque in Type 2 Diabetes: A Real-World Study

Abstract: Background: Controversies concerning the association between insulin therapy and atherosclerotic lesions in type 2 diabetes mellitus (T2DM) remain to exist. The purpose of this study was to investigate whether insulin therapy in T2DM patients is linked with the increased risk of carotid atherosclerosis in real-world settings.Methods: We retrospectively enrolled 2,356 hospitalized patients with T2DM, including 1,716 subjects receiving insulin therapy and 640 subjects without receiving insulin therapy. Carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In addition, the levels of TG and LDL-C in the T2DM group were higher than those in the NC group. The free fatty acids produced by TG were able to further reduce insulin sensitivity, forming a vicious circle between TG levels and insulin resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of TG and LDL-C in the T2DM group were higher than those in the NC group. The free fatty acids produced by TG were able to further reduce insulin sensitivity, forming a vicious circle between TG levels and insulin resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The hospital ethical review committee approved this study [approved number: 2018-KY-018(K)], with written consent obtained from all participants. Inclusion criteria incorporated T2DM diagnosed in accordance with the WHO criteria, age ≥ 17 years old, complete clinical information and biochemical parameters, and available abdominal ultrasound findings ( 25 ). After excluding the patients with disorders related to iron metabolism such as hemochromatosis, iron-deficiency anemia, menstruation within a week, and blood transfusion or donation recently; those with liver diseases caused by drugs, viral hepatitis, and other reasons excluding alcohol; and those with other serious systemic diseases or infectious diseases, 1,467 patients were classified into four groups according to the serum iron quartiles.…”
Section: Methodsmentioning
confidence: 99%
“…The following data were collected at admission as previously described: hypertension history, diabetes duration (DD), alcohol intake, smoking habits, use of lipid-lowering drugs (LLDs), metformin, insulin sensitizers, insulin or insulin analogs (IIAs), and physical data including height, waist and hip circumference, weight, and blood pressure ( 10 , 11 ). Specifically, the definitions of hypertension, obesity, smoking, and alcohol status were described in our previous studies ( 11 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The TyG index is a reliable alternative marker for IR, which may play an important role in inferring the relationship between TyG and carotid plaque. Many previous studies have demonstrated that IR plays an important role in the development of atherosclerosis and advanced plaque, by promoting increased synthesis and release of lipoproteins, growth and proliferation of vascular smooth muscle cells, and enhanced transport of LDL-C to arterial smooth muscle cells and inflammation ( 9 , 10 , 28 30 ). In addition, IR is associated with a group of metabolic abnormalities known as insulin resistance syndrome.…”
Section: Discussionmentioning
confidence: 99%